Electric-field-induced structure and domain texture evolution in PbZrO3-based antiferroelectric by in-situ high-energy synchrotron X-ray diffraction. (1st February 2020) - Liu, Hui; Fan, Longlong; Sun, Shengdong; Lin, Kun; Ren, Yang; Tan, Xiaoli; Xing, Xianran; Chen, Jun
Abstract: Antiferroelectrics (AFEs) have a great potential for modern electronic devices by virtue of the large strain during the antiferroelectric-to-ferroelectric (AFE-FE) phase transition under external electric fields. Although the fascinating macroscopic properties of AFE materials have been extensively studied, it is still unclear how the underlying structure evolution engenders their defining properties. Here we employ an electric biasing in-situ high-energy synchrotron X-ray diffraction technique to reveal the phase, domain texture, and lattice evolution in a high performance PbZrO3 -based AFE material. During the reversible AFE-FE transition triggered by electric fields, the evolution of the superstructure for AFE pseudo-tetragonal and FE rhombohedral phase is found to display strong dependence on the angle with respect to the field direction. In contrast to previous prediction, it is found that there is no obvious domain reorientation in the AFE phase, when the system is far away from the AFE-FE transitions. The electric-field-induced FE rhombohedral phase exhibits an unusual microscopic behavior, distinguished from the normal one, presenting small changes in domain texture and lattice strain with electric field, and leading to a small piezoelectric response. The longitudinal, transverse, and volume strains estimated from the XRD peak profiles are well consistent with the macroscopic strain measurements. It is demonstrated that the large strain arises from the structural change associated with anisotropic lattice strain and highly preferential domain reorientation during the AFE-FE transitions. The AFE-FE switching sequence is constructed based on the present study, which provides a further understating of AFE materials. Graphical abstract: Image, graphical abstract